Severe drought limits trees in a semi‐arid savanna. Issue 11 (28th August 2019) - Case, Madelon F.; Wigley‐Coetsee, Corli; Nzima, Noel; Scogings, Peter F.; Staver, A. Carla
Abstract: Increasingly frequent and severe droughts under climate change are expected to have major impacts on vegetation worldwide. However, research to date has focused on tree vulnerability to drought in forests. Less is known about trees and drought in savannas, where a sparse tree layer coexists with grass. These tree–grass interactions (often mediated by fire and herbivory) shape savanna tree ecology, and confound predictions of how strongly drought might affect trees. On the one hand, drought is physiologically stressful, which could harm trees and be exacerbated by herbivore impacts; on the other hand, trees adapted to semiarid savannas might be relatively drought tolerant, and the considerable impacts of drought on grass could even benefit trees via reduced grass competition and fire risk, especially in the year following a drought. Here, we sought to understand the net effects of severe drought on the savanna tree layer, and how fire and herbivory mediate these effects. We monitored tree growth, mortality, and community structure for 2 yr within existing long‐term fire and herbivory experiments across a drought‐severity contrast, following a major drought in Kruger National Park, South Africa. Overall, severe drought was a major stressor for trees. Tree mortality rates in most species increased by an order of magnitude in the year following drought, and slower growth rates for some persisted for 2 yr. At the community level, this translated into substantial decreases in tree densities. Herbivory and fire did little either to mitigate or exacerbate drought effects on trees, and overall, drought swamped effects of herbivory and fire that have otherwise been observed. However, species differed in their responses to drought, with some dominant encroaching species especially vulnerable. We suggest that increasing drought frequency and severity could drastically alter savanna vegetation by repeatedly killing off trees.